Redesign methods and guidelines for additive manufacturing in aerospace industries - Hui, Yijian (Nanyang Technological University, 2020)
With dreams of space exploration increasing through improving technology and media outlets, human desires for the unknown is lit once more. However, to further explore the unknown, a forerunner is required in the form of CubeSats. Currently, the International Space Station has been researching on In Space Additive Manufacturing to quench this thirst of the human population. Additive Manufacturing has unleashed its hidden potential in its abilities to function in a 0-gravity environment. This could represent the possibilities of satellites being manufacture in space, skipping the entire process of launching from ground zero. This report will serve as a documentation of the process and results obtained in this Final Year Project. The project is an attempt in making a printable thruster system for the CubeSat in the hope of playing a part in this space exploration journey.